Estimating the Impact of the Macroeconomic Indicators Shocks on KSA Non-oil Exports 1970-2019: (SVAR) Analysis and (NARDL) Assessment - Fadol, Hassan Tawakol A. (International Journal of Economics and Financial Issues, 2020)
Studies employ various methods to explain the presence of the Impact of the macroeconomic indicators shocks on non-oil exports, including applying models to the case of emerging economies. However, the non-oil exports have different determinants in some countries. To revisit this puzzle, we analyzed the Estimating the Impact of the macroeconomic indicators shocks on KSA non-oil exports: (SVAR) analysis and (NARDL) assessment. Short run and long run shocks between the selected variables and result’s is checked through the SVAR, NARDL model. Our results confirm co-integration, positive shocks results show that macroeconomic indicators shocks have significantly influence on non-oil exports. The empirical results based on SVAR, NARDL most relationships are weak and negative except for non-oil exports, monetary reserves. Here we can observe the elasticities or contemporaneous relations between variables. We see negative relations between non-oil exports and GDP, Exchange Rate and inflation in the same interval, while an increase in non-oil exports has nearly no impact on both GDP, Exchange Rate and inflation. The results provide statistically, economics supported evidence that can guide policy makers regarding action priorities and identify other opportunities to facilitate reducing the Impact of the macroeconomic indicators shocks on non-oil exports in Saudi Arabia. Keywords: Non-Oil Exports, Inflation Rate, Monetary Reserves, GDP, SVAR, NARDL JEL Classifications: E31, E52 DOI: https://doi.org/10.32479/ijefi.10420